Wordwall Media Game In Mastery Of Arabic Vocabulary - Saariah, Saariah; Azzahra, Luthfi Qolbi; syarafina, Dea agta; Nasiruddin, Nasiruddin; Jariah, Ainun (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This study aims to provide insights into innovative, creative, and educational approaches in Arabic language learning in the digital era, with a focus on using Wordwall as a medium for mastering Arabic vocabulary. The study employs a qualitative research design through a library research approach, utilizing data from literature that discusses the use of Wordwall games in Arabic language education. Data collection techniques include documentation of journals related to Wordwall, while the data analysis technique used is content analysis. The findings of the study indicate that Wordwall is effective in enhancing students' ability to recall and comprehend Arabic vocabulary. The application offers various engaging features, such as diverse game templates, the ability to edit and customize content, and ease of sharing activities, all of which can motivate students and facilitate the understanding of complex concepts. Therefore, the use of Wordwall has proven to overcome challenges in teaching Arabic vocabulary and contribute to improving students' learning outcomes. The implication is that using Wordwall can help both students and educators achieve more effective and innovative learning goals in this digital era.